2020
DOI: 10.24996/ijs.2020.61.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Human Pulmonary Activation-Regulated Chemokine (CCL18/PARC) and Alkaline Phosphatase (ALP) Levels in Iraqi Patients with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is one of the chronic inflammatory autoimmune diseases which occurs as a result of unknown reasons. This study was conducted at Baghdad Teaching Hospital/City of Medicine, where blood samples were taken from 60 Iraqi patients with RA (49 females and 11 males) and these patients were matched by age and sex with 20 healthy controls (16 females and 4 males). Patients with RA were diagnosed by a consultant rheumatologist according to ACR / EULAR criteria in 2010. In this study the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The hypoxia modulation cellular bioenergetics by inducing dysfunction of mitochondrial and promoting a switch to glycolysis, that leading to abnormal angiogenesis [30]. The current study agrees with a previous report which recorded significantly elevated serum levels of biomarkers in RA patients than those in the control group (p≤0.001) [31].…”
Section: Discussionsupporting
confidence: 92%
“…The hypoxia modulation cellular bioenergetics by inducing dysfunction of mitochondrial and promoting a switch to glycolysis, that leading to abnormal angiogenesis [30]. The current study agrees with a previous report which recorded significantly elevated serum levels of biomarkers in RA patients than those in the control group (p≤0.001) [31].…”
Section: Discussionsupporting
confidence: 92%
“…During hypoxia related anemia, mediators such as PDGF-BB, which is released by different cell types, suppress hepcidin. Hepcidin levels are decreased by a special mechanism in low-risk myelodysplasia with ringed sideroblasts, a clonal disorder due to mutations of the spliceosome gene SF3Bl 51 . Scientists revealed that iron accumulation in the mitochondria, could lead to ineffective erythropoiesis and systemic iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…Through a variety of mechanisms, TN-C promotes both adaptive and innate immune responses in arthritic joints. TN-C's C-terminal gFG induces the pro-inflammatory cytokines and chemokines release in autoimmune disease patients such as RA [10], which increases the risk of osteoporosis around the afflicted joint, erosive synovitis, bone damage, and cartilage deterioration [11,12].…”
Section: Introductionmentioning
confidence: 99%